Assessment of electric field on hdpe-natural rubber biocomposite with sphere to sphere electrode configuration - Abdul Azlen, Farah Atiqah (2021)
Rapid growth of high voltage technology gives the opportunity to engineer to do a study on the environmental protection. Development of the design and manufacture of polymer insulation materials today make polymer insulation better because polymer insulators have a strength-to weight ratio which is larger than porcelain so that it can reduce manufacturing costs. This project is represented a study to analyse the electric field intensity of High Density Polyethylene (HDPE) when added with 10%, 20% and 30% of different types of bio-filler such as coconut coir fibre, pineapple leaves fibre, and oil palm empty fruit bunch. This can be accomplished by creating a two-dimensional (2D) axisymmetric electrostatic model by using the Finite Element Method Magnetics (FEMM) 4.2 software. Based on the results actualize, the inclusion of bio-filler in HDPE increased the maximum electric field intensity when compared with unfilled HDPE. The electric field intensity also varied with the different percentages loading of biocomposite and their permittivity. As a result, the maximum electric field intensity was much lower for HDPE added with a 10% loading of the oil palm empty fruit bunch. Hence, oil palm empty fruit bunch was the best composition as it tends to improve the dielectric properties since it has a lower electric field intensity at the top sphere electrode as compared to other compositions.